2016
DOI: 10.1080/10615806.2016.1157170
|View full text |Cite
|
Sign up to set email alerts
|

Associations of ethnic discrimination with symptoms of anxiety and depression among Hispanic emerging adults: a moderated mediation model

Abstract: Background and Objectives Emerging adulthood is often marked with elevated symptoms of anxiety and depression. Hispanic emerging adults may face cultural stressors such as ethnic discrimination that further increase levels of anxiety and depression symptoms. The study aims were to examine if (a) self-esteem mediated effects of ethnic discrimination on symptoms of anxiety and depression, and (b) if gender moderated the indirect effects of discrimination. Design The study design was cross-sectional self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
(32 reference statements)
1
28
0
Order By: Relevance
“…A growing body of literature has documented the mental health effects of discrimination in Latino populations specifically (Finch, Kolody, and Vega 2000; Flores et al 2008; Gee et al 2006; Basáñez et al 2013; Behnke et al 2011; Cano et al 2016; Davis et al 2016; Delgado et al 2011; Roblyer et al 2016). Our results support the findings of these prior studies, which suggest that Latinos in the US may be particularly vulnerable to discrimination’s adverse effects on mental health due to the multiple avenues by which discrimination may enter their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has documented the mental health effects of discrimination in Latino populations specifically (Finch, Kolody, and Vega 2000; Flores et al 2008; Gee et al 2006; Basáñez et al 2013; Behnke et al 2011; Cano et al 2016; Davis et al 2016; Delgado et al 2011; Roblyer et al 2016). Our results support the findings of these prior studies, which suggest that Latinos in the US may be particularly vulnerable to discrimination’s adverse effects on mental health due to the multiple avenues by which discrimination may enter their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that social structures of inequality embody the unequal distribution of resources and opportunities, a low status within them may itself be a source of stressful life conditions (Pearlin, Schieman, Fazio, & Meersman, 2005). For instance, immigrant status has been found to be associated with acculturative stressors which include: adapting to a new environment, language barriers, severe economic hardship, occupational related exploitation, residential instability, legal status stressors, discrimination, and loss of social support (Arbona et al, 2010;Cano et al, 2016;Cuellar, Bastida, & Braccio, 2004;Sullivan & Rehm, 2005;Torres & Wallace, 2013).…”
Section: Migration History and Gendermentioning
confidence: 99%
“…1 However, a large body of public health research on discrimination and psychological well-being challenges the implied link between discrimination and increased activism (see Figure 1). Numerous studies have shown that exposure to unfair treatment on the basis of race, ethnicity, religious affiliation or sexual orientation is associated with feelings of inferiority, insecurity, powerlessness and depression (Almeida et al 2009; Banks, Kohn-Wood, and Spencer 2006; Branscombe, Schmitt, and Harvey 1999; Cano et al 2016; Dion and Earn 1975; Hodge, Zidan, and Husain 2015; Noh and Kaspar 2003; Padela and Heisler 2010), and that adverse mental health outcomes, such as depression, reduce the likelihood of voting (Ojeda 2015; Ojeda and Pacheco 2017). How do we reconcile these differences?…”
mentioning
confidence: 99%